Examining the Relative Contribution of Maslow's Motivational Dimensions to Employee Performance - Ade Setiadi (International Journal of Science Education and Cultural Studies, 2023)
The motivation of employees is a known factor of organizational performance. However, there is still a lack of empirical evidence on the relative contribution of different motivational dimensions to employee performance in public sector organizations. This study examines the role of five dimensions of Maslow’s Hierarchy of Needs, i.e. physiological needs, safety needs, social needs, esteem needs, and self-actualization needs to employee performance in the Department of Education and Culture of Indramayu Regency, Indonesia. The study used a quantitative research design where data was collected through survey, structured questionnaires from 54 employees. The validity and reliability of the research instrument was established before data analysis. Multiple linear regression was used to determine the contribution of each motivational dimension to employee performance. The results indicated that the five dimensions of motivation together contribute to employee performance, with esteem needs having the highest contribution among the motivation dimensions. The findings pointed out the importance of applying comprehensive motivational approaches that address the employees’ physiological, safety, social, esteem and self-actualisation need to improve employee performance. This study is a contribution to the application of Maslow's motivational theory in the public sector and has practical implications for human resource management in government institutions.